2020
DOI: 10.1128/msystems.00905-19
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome Mining Reveals Hidden Genomic Diversity of Pelagimyophages in Aquatic Environments

Abstract: The SAR11 clade is one of the most abundant bacterioplankton groups in surface waters of most of the oceans and lakes. However, only 15 SAR11 phages have been isolated thus far, and only one of them belongs to the Myoviridae family (pelagimyophages). Here, we have analyzed 26 sequences of myophages that putatively infect the SAR11 clade. They have been retrieved by mining ca. 45 Gbp aquatic assembled cellular metagenomes and viromes. Most of the myophages were obtained from the cellular fraction (0.2 μm), indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 118 publications
3
48
0
Order By: Relevance
“…To our knowledge, no genomes of viruses infecting freshwater Methyloglobulus have been described. The gene content of these viruses included proteins involved in production of curly polymers and the ribosomal protein S21, which were previously detected in SAR11 phages [23] and a putative Polynucleobacter phage [5]. Interestingly, these viruses did not encode the diverse array of AMGs described for the methylotroph viruses from VP_139 and VP_266, possibly because these sequences do not represent the complete viral genome.…”
Section: Baikal Viruses Infecting Methylotrophs Interfere With Methylmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, no genomes of viruses infecting freshwater Methyloglobulus have been described. The gene content of these viruses included proteins involved in production of curly polymers and the ribosomal protein S21, which were previously detected in SAR11 phages [23] and a putative Polynucleobacter phage [5]. Interestingly, these viruses did not encode the diverse array of AMGs described for the methylotroph viruses from VP_139 and VP_266, possibly because these sequences do not represent the complete viral genome.…”
Section: Baikal Viruses Infecting Methylotrophs Interfere With Methylmentioning
confidence: 99%
“…Among those assigned as viruses of bacteria (i.e., bacteriophages), the majority of sequences were predicted to infect Actinobacteriota (640), followed by Gammaproteobacteria (235), Bacteroidota (241) and Cyanobacteria (226), and Alphaproteobacteria (106). Although less frequent, some sequences were predicted to be derived from viruses that infect taxa with few or no isolated viruses such as Nitrospirota (9), Patescibacteria (14), and Crenarchaeota (23).…”
Section: Taxonomic Classification and Predicted Hosts Of Baikal Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other pelagiphage sequences reported in the literature were retrieved from culture‐independent single‐cell genomic or metagenomic studies (Mizuno et al ., 2013; Mizuno et al ., 2016; Martinez‐Hernandez et al ., 2017; Zaragoza‐Solas et al ., 2020). For example, a recent study reported 26 putative pelagimyophages that were retrieved from cellular metagenomes and viromes, revealing the genomic diversity of pelagimyophages (Zaragoza‐Solas et al ., 2020), and an uncultured single‐virus contig vSAG 37‐F6 has been identified as a pelagiphage (Martinez‐Hernandez et al ., 2017). To further explore the diversity of pelagiphages and establish more representative SAR11‐pelagiphage model systems for future investigations on pelagiphage genomic evolution and phage–host interactions, efforts are still needed to isolate and characterize more pelagiphages.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid development of viral metagenomics and bioinformatics has provided an opportunity to overcome these obstacles [5,6]. In recent years, large amounts of viral genomes, most of which are novel bacteriophages, have been identi ed from a variety of environments, such as marine environments [7,8], freshwater environments [9], hot spring mats [10], rhizosphere soils [11], and mangroves [12]. The ndings of these studies indicated that bacteriophages interacting with their hosts (bacteria and archaea), acted as key partners in multiple ecosystems.…”
Section: Introductionmentioning
confidence: 99%